Has the pandemic resulted in a renewed and improved focus on heath inequalities in England? A discourse analysis of the framing of health inequalities in national policy - Beth Capper; John Ford; Mike Kelly (Elsevier, 2023)
Objectives: The COVID-19 pandemic rapidly exacerbated health inequalities in England. Policy makers sought to ameliorate its impact. This paper aims to identify how health inequalities were framed in national policy documents published in England during the pandemic and how this impacts the framing of policy solutions. Study design: Discourse analysis of selected national policy documents. Methods: First, we identified relevant national policy documents through a broad search and eligibility criteria to identify illustrative policy documents. Second, we undertook a discourse analysis to understand the framing and constitution of health inequalities and consequent solutions within them. Third, we used existing health inequalities literature to critique the findings. Results: Based on analysis of six documents, we found evidence of the idea of lifestyle drift with a marked disjunction between the acknowledgement of the wider determinants of heath and the policy solutions advocated. The target population for interventions is predominantly the worst off, rather than the whole social gradient. Repeated appeals to behaviour change indicate an inherent individualist epistemology. Responsibility and accountability for health inequalities appears delegated locally without the power and resource required to deliver. Conclusion: Policy solutions are unlikely to address health inequalities. This could be done though through (i) shifting interventions towards structural factors and wider determinants of health, (ii) a positive vision of a health equitable society, (iii) a proportional universalism in approach and (iv) a delegation of power and resource alongside responsibility for delivering on health inequalities. These possibilities currently remain outside of the policy language of health inequalities.